Fretting Analysis of Aluminium 6061 Reinforced With Graphene - M.R, Srinivasa.; S Rammohan, Y; Irfan, Zahid (International Journal of Engineering and Technology, 2018)
The application of Aluminium alloys becomes significant and most wide in the field of aviation industry. Aluminium 6061, because of its pro mechanical characteristics. Graphene is one of the allotropic forms of Carbon which is abundantly available in nature. The high tensile strength and low density of graphene is the added advantage as it is used as a reinforced material with Aluminium 6061.Â Graphene was found to beÂ a more suitableÂ reinforcing materialÂ thatÂ improves tribological properties ofÂ metal. Composite materialsÂ are mixturesÂ of variousÂ parent materialsÂ resulting inÂ the formation of materials havingÂ a mixÂ of variedÂ desired properties like low weight,Â largerÂ stiffness, higher specific strength etc. The composite materialsÂ soÂ obtained invariably have superior properties to their parental ones.Â SoÂ these materials becomeÂ a reallyÂ enticingÂ noticeÂ forÂ higherÂ strengthenedÂ materialÂ for industrial sector. This paperÂ primarilyÂ focuses on distinctive effects of utilizing Graphene as reinforcement for Al-6061in the view of tribological characteristics. Graphene has outstanding mechanical and physical properties,Â creatingÂ itÂ a perfect reinforcement material forÂ lightweightÂ weight and high strength metal matrix composites (MMC) like Al-6061. Fabrication, being aÂ importantÂ step,Â because itÂ controls the microstructure, thatÂ successivelyÂ determines the properties of theÂ material, was conducted by stir casting. Stir castingÂ additionallyÂ helpedÂ within theÂ dispersion of Graphene uniformlyÂ within theÂ metal matrix composite.Â To analyze the effect of tribological parameters damage resistance of the metal matrix composite, linear reciprocating tribometer was used. Â Â